An adult juvenile xanthogranuloma in the buccal mucosa - Ching-Yi Chen; Cheong-Lin Sung; Mu-Yen Hsieh; Wen-Chen Wang; Li-Min Lin; Yuk-Kwan Chen (Elsevier, 2015)
Juvenile xanthogranulomas (JXGs) are a type of non-Langerhans cell histiocytosis that commonly affects infants and children. Adult oral JXGs are very rare. A 32-year-old Taiwanese male presented with the chief complaint of a solitary, firm, painless, non-tender swelling over the right buccal mucosa for about 2 weeks. An excisional biopsy of the lesion revealed a mixture of histiocytes, inflammatory cells, and Touton giant cells, and immunohistochemical positivity for CD68 and negativity for S-100 and CD1a confirmed the diagnosis of a JXG. Therefore, the current case report documents, to our knowledge, the first occurrence of an adult oral JXG in the buccal mucosa. It is also the first case of an adult oral JXG to be reported from Taiwan. The clinical characteristics of adult oral JXGs are also briefly reviewed.